The effectiveness of immersive virtual reality in physical recovery of stroke patients: A systematic review - Patsaki, Irini; Dimitriadi, Nefeli; Despoti, Akylina; Tzoumi, Dimitra; Leventakis, Nikolaos; Roussou, Georgia; Papathanasiou, Argyro; Nanas, Serafeim; Karatzanos, Eleftherios (Frontiers in Systems Neuroscience, 2022)
Background: Over the past few years technological innovations have been increasingly employed to augment rehabilitation of stroke patients. Virtual reality (VR) has gained attention through its ability to deliver a customized training session, and to increase the patients’ engagement. Virtual reality rehabilitation programs allow the patient to perform a therapeutic program tailored to his/her needs while interacting with a computer simulated environment. Purpose: To investigate the effectiveness of fully immersive rehabilitation program using a commercially available Head Mounted Display in stroke patients. Methods: A systematic search was conducted in three databases: Pubmed, Google scholar and Pedro. Four hundred, thirty two references were identified. The key words used for the literature search were in English and were the following ones: immersive, virtual reality, neurorehabilitation, stroke, head mounted display. Additional, applicable articles were identified through screening reference lists of relevant articles. Results: Only 12 studies used Head Mounted Display for immersing the patient into the virtual word and included. Apart from the feasibility of this new technology, a range of benefits were identified, especially in terms of functional ability as measured by FIM or Barthel, the Action Research arm Test, Box and Block Test, Fugl-Meyer assessment of physical performance, strength and balance outcomes. Conclusion: The results from this review support the potential beneficial effect of fully immersive virtual reality in rehabilitation of stroke patients, maximizing recovery through increased motivation and adherence.